Erratum: Alkhatib et al., “Promiscuous G-protein-coupled receptor inhibition of transient receptor potential melastatin 3 ion channels by Gβγ subunits” - Alkhatib, Omar; Freichel, Marc (The journal of neuroscience, 2020)
In the article “Promiscuous G-Protein-Coupled Receptor Inhibition of Transient Receptor Potential Melastatin 3 Ion Channels by Gβγ Subunits,” by Omar Alkhatib, Robson da Costa, Clive Gentry, Talisia Quallo, Stuart Bevan, and David A. Andersson, which appeared on pages [7840-7852][1] of the
Gesehen am 11.11.2020